Exploring Anatomical Variations in the Median Nerve-Axillary and Brachial Artery Relationships - Sthapak, Eti; Pasricha, Navbir (Medical Science: Trends and Innovations Vol. 7, 2025)
Introduction: Variations in the course of nerves and vessels of the upper limb are relatively common and hold significant clinical relevance. The knowledge of these variations is valuable to prevent iatrogenic injuries to vascular, plastic, general surgeons, anesthesiologist and orthopedic surgeons. The brachial artery serves as a primary arterial supply for the upper limb, and its relationship with the median nerve is of particular interest. In the arm, the median nerve initially lies lateral to the brachial artery near the insertion of coracobrachialis muscle, then crosses anteriorly, continuing medially in the cubital fossa. Aim: The present study aims to assess anatomical variations in the course and relationship of the median nerve to axillary and brachial artery in the arm. Materials and Methods: The present study was carried out over four years on a sample of 60 cadavers (120 upper limbs). Proper cadaveric dissection was done in the Department of Anatomy, Dr. RML Institute of Medical Sciences, Lucknow, India. Observation and Results: It was observed that in 10% of the cadavers, median nerve crossed behind the brachial artery at the mid-arm. In the rest of the cases, the median nerve entered the arm at first lateral to the brachial artery and near the insertion of coracobrachialis it crossed in front of the artery from lateral to medial side. Conclusion: Understanding the variations in the brachial artery and its relationship with median nerve is crucial for clinical and surgical practice. This knowledge is essential for surgeons and radiologists when interpreting angiographic images, vascular and re-constructive surgeries and treating compressive neuropathies.